The high-status compassion bias: when and why do people assist high- and low-status victims? - Matos Devesa, Andrea Soledad (2022)
Does the social status of victims in emergencies play a role in bystanders’ compassionate orientations towards them? In this thesis, I examine the hitherto unexplored proposition that bystanders may be more inclined toward expressing compassion in favor of victims who signal high (rather than low) social status. I tested this novel thesis in six experiments that systematically varied the social status of victims of fabricated emergencies and afterward measured their compassion to investigate whether the expression of this emotion was stronger for higher (relative to lower) status victims. In doing so, I considered a variety of situational and individual difference factors that could enable (or constrain) a compassion bias favoring victims from high-status backgrounds.